The Effectiveness of Dream Analysis in Reducing Idiopathic Nightmares by Hermeneutic Single Case Efficacy Design (HSCED) - Masoud Bagheri; Maryam Arabnejad khanuki (Journal of Qualitative Research in Health Sciences, 2022)
Introduction: Nightmares are prevalent parasomnia associated with various forms of psychological distress in both the clinical and general population. The aim of the current study was to explain the experiences of the client regarding the effects of nightmares and the process of dream analysis treatment on idiopathic nightmares.Methods: In this qualitative study, the client was a 34-year-old woman who participated in 8 sessions of dream analysis treatment. Based on DSM-5, she had the criteria of a nightmare. Rich data were collected from her. The hermeneutic method was used to collect and analyze quantitative and qualitative data. This study used a simple method to perform the hermeneutic analysis that requires only one person while maintaining its validity.Results: The findings showed that the frequency of nightmares decreased during the treatment. The client changed significantly during the treatment, and the dream analysis was also responsible for this change. According to Bohart’s criteria, the client changed with at least 72% confidence and with 87% confidence this change in relation to external factors happened as a result of the treatment. Useful therapeutic factors included examining the hidden meaning of nightmares, expressing emotions, self-awareness, and reducing helplessness.Conclusion: The results of the interventions showed that treatment processes made changes in the client that were unexpected and important to her and these changes would not have happened without the treatment. This method, in addition to exposing the person to the content of the nightmare, leads to the discovery and decoding of the content of the nightmare and understanding of its message to resolve conflicts.